2014
DOI: 10.1039/c4ra07305c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and DFT study on the indium-mediated synthesis of benzophenones via arylstannanes

Abstract: A DFT analysis was performed with the aim to explaining the narrow scope of the indium-promoted reaction of aroyl chlorides with arylstannanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Very recently, we have reported a theoretical interpretation with DFT methods of the limited experimental scope found with some aroyl chlorides in the solvent-free, indiumpromoted reaction with arylstannanes. 8 Based on these findings, and taking into account that the known low bond dissociation energy of benzylic C-Sn bond facilitates homolytic reactions, a plausible mechanism for the reactions examined in the current work is outlined in Scheme 1.…”
Section: Resultsmentioning
confidence: 93%
“…Very recently, we have reported a theoretical interpretation with DFT methods of the limited experimental scope found with some aroyl chlorides in the solvent-free, indiumpromoted reaction with arylstannanes. 8 Based on these findings, and taking into account that the known low bond dissociation energy of benzylic C-Sn bond facilitates homolytic reactions, a plausible mechanism for the reactions examined in the current work is outlined in Scheme 1.…”
Section: Resultsmentioning
confidence: 93%
“…In order to contribute to the rational design of more selective and active catalysts, it is crucial to have an in-depth understanding of the mechanistic aspects involved in each catalytic process. To this end, and inspired by our permanent interest in the use of computational methods for unveiling the main mechanistic aspects of organic transformations, 24 specially those promoted by supported metal nanocatalysts, 25 we present herein a computational theoretical study, based on DFT methods, to shed light on the high stereoselectivity observed in the hydrothiolation of activated alkynes with thiols bearing a catechol group catalysed by CuNPs/TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In connection with our continuing effort to explore the synthetic potential of organotin compounds [17], and given that many of these reagents have become invaluable tools in organic chemistry, we envisioned that the use of TBSnN 3 , in place of TMSN 3 , on Moses's methodology, would also achieve the in-situ azidodediazoniation pathway and then, after an appropriate workup, it could be recovered and recycled from the low volatile and highly stable tributyltin byproducts.…”
Section: Introductionmentioning
confidence: 99%